2022
DOI: 10.3390/fractalfract6030159
|View full text |Cite
|
Sign up to set email alerts
|

Robust Control for Variable-Order Fractional Interval Systems Subject to Actuator Saturation

Abstract: In this paper, a class of variable-order fractional interval systems (VO-FIS) in which the system matrices are affected by the fractional order is investigated. Firstly, the sufficient conditions for robust stability of a VO-FIS with a unified order range of ν(σ)∈(0,2) are proposed. Secondly, the stabilization conditions of a VO-FIS subject to actuator saturation are derived in terms of linear matrix inequalities (LMIs). Then, by using the proposed algorithm through an optimization problem, the stability regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Thus, using the definitions of e p 1 , e p 2 , and e δ1 , and using ( 14), (32), and (41), we obtain:…”
Section: V(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using the definitions of e p 1 , e p 2 , and e δ1 , and using ( 14), (32), and (41), we obtain:…”
Section: V(s)mentioning
confidence: 99%
“…This proves the bounded nature of the system as time approaches infinity. Such an eigenproblem has been previously used to validate the stability of several control systems, as described in [29][30][31][32].…”
Section: V(s)mentioning
confidence: 99%
“…In the research of [9], the authors showed that real inputs exhibit long-range dependence: the behavior of a real process after a given time t depends on the entire history of the process up to time t, the classical examples are presented in finance [10][11][12], that is why the researchers considered controlled problems not only with white noise or standard Brownian motion, but also with fractional type noise such as the fractional Brownian motion [13,14]. The applications of fractional case can be seen in [15][16][17][18]. Let us take [13] for the example: The authors considered the controlled drift estimation problem in fractional Ornstein-Ulenbeck (FOU) process:…”
Section: Introductionmentioning
confidence: 99%
“…In [4], sufficient conditions for variable-order fractional interval systems with orders (0, 2) subject to actuator saturation for stabilization criterion in terms of LMIs were given. Based on the stability conditions, this article estimated the stability domain of the system by solving an optimization problem in terms of LMIs, and the eigenvalues of the system matrix are restrained in the right half of the plane.…”
mentioning
confidence: 99%